2021
DOI: 10.1159/000517762
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Chromosome 16 Copy Number Variation

Abstract: Chromosome 16 is one of the gene-rich chromosomes; however, approximately 10% of the chromosome 16 sequence is composed of segmental copies, which renders this chromosome instable and predisposes it to rearrangements via frequent nonallelic homologous recombination. Microarray technologies have enabled the analysis of copy number variations (CNV), which may be associated with the risk of developing complex diseases. Through comparative genomic hybridisation in 1,298 patients, we detected 18 cases with chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The chromosomal trisomy was most often detected in chromosome 16, this is consistent with prior studies ( 30 ). Chromosome 16 is gene-rich but unstable due to a 10% segmental copy sequence, making it prone to frequent non-allelic homologous recombination and gene rearrangements ( 34 ). Advanced maternal age is a widely recognized risk that increases the risk of chromosomal abnormalities and spontaneous miscarriage, with the incidence of chromosomal aneuploidy being higher in women over 35 years old ( 35 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomal trisomy was most often detected in chromosome 16, this is consistent with prior studies ( 30 ). Chromosome 16 is gene-rich but unstable due to a 10% segmental copy sequence, making it prone to frequent non-allelic homologous recombination and gene rearrangements ( 34 ). Advanced maternal age is a widely recognized risk that increases the risk of chromosomal abnormalities and spontaneous miscarriage, with the incidence of chromosomal aneuploidy being higher in women over 35 years old ( 35 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, differences in brain structure and some significant MRI findings of people with 16p11.2 microduplication syndrome were described. Deletions and duplications of the 16p11.2 locus have already been associated with changes in brain anatomy [ 25 , 26 ]. Within those diagnosed with a duplication, microcephaly, cerebral white matter or corpus callosum abnormalities and ventricular enlargement were also observed, but less frequently than speech articulation abnormalities, hypotonia, abnormal agility, sacral dimples and seizures or epilepsy [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that human-induced pluripotent stem cell-derived neurons from 16p11.2 duplication carriers display corresponding features with reduced size/dendrite length in neurons [ 3 ]. Furthermore, the reduced cortical surface area has been reported, and analyses of cortex anatomies revealed reduced cortical thickness in both 16p11.2 deletion and duplication carriers [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cause of phenotypic diversity in patients with 16p13.11 microdeletion is still unclear and detailed analysis is warranted [21]. 16p13.11 microduplication has been linked to autism and neuropsychiatric disorders, including schizophrenia, attention deficit hyperactivity disorder, and intellectual disability [11,[22][23][24][25]. In fact, the influence of 16p13.11 microduplication is not without controversy, and some studies have reported it as a rare benign variant [26].…”
Section: Discussionmentioning
confidence: 99%